2014
DOI: 10.1002/chem.201400377
|View full text |Cite
|
Sign up to set email alerts
|

Binding of a Ruthenium Complex to a Thioether Ligand Embedded in a Negatively Charged Lipid Bilayer: A Two‐Step Mechanism

Abstract: The interaction between the ruthenium polypyridyl complex [Ru(terpy)(dcbpy)(H2O)](2+) (terpy = 2,2';6',2"-terpyridine, dcbpy = 6,6'-dichloro-2,2'-bipyridine) and phospholipid membranes containing either thioether ligands or cholesterol were investigated using UV-visible spectroscopy, Langmuir-Blodgett monolayer surface pressure measurements, and isothermal titration calorimety (ITC). When embedded in a membrane, the thioether ligand coordinated to the dicationic metal complex only when the phospholipids of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…In the exemplary case of the adsorption of one dicationic functional molecule such as [Ru(tpy)(bpy)(OH 2 )] 2+ (tpy = 2,2 0 :6 0 ,2 00 -terpyridine) onto negatively charged DMPG based lipid bilayers involves the desorption of two Na + from the bilayer surface. 51 Depending on the respective ion pairing and solvation energies and entropies, this process can either be endothermic or exergonic due to a significant energetic contribution from the entropy term of ion release (two equivalents of Na + cations) to the bulk. 51…”
Section: Adsorption Of Active Molecules At the Water-membrane Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…In the exemplary case of the adsorption of one dicationic functional molecule such as [Ru(tpy)(bpy)(OH 2 )] 2+ (tpy = 2,2 0 :6 0 ,2 00 -terpyridine) onto negatively charged DMPG based lipid bilayers involves the desorption of two Na + from the bilayer surface. 51 Depending on the respective ion pairing and solvation energies and entropies, this process can either be endothermic or exergonic due to a significant energetic contribution from the entropy term of ion release (two equivalents of Na + cations) to the bulk. 51…”
Section: Adsorption Of Active Molecules At the Water-membrane Interfacementioning
confidence: 99%
“…51 Depending on the respective ion pairing and solvation energies and entropies, this process can either be endothermic or exergonic due to a significant energetic contribution from the entropy term of ion release (two equivalents of Na + cations) to the bulk. 51…”
Section: Adsorption Of Active Molecules At the Water-membrane Interfacementioning
confidence: 99%
“…The use of light as a trigger for the activation of metal-based anticancer agents has been actively researched over the last decades. In combination with ruthenium­(II) complexes, light can be used either to drive the formation of reactive oxygen species through the sensitization of oxygen in photodynamic therapy (PDT) or to uncage photoactivatable complexes through ligand photosubstitution in photoactivated chemotherapy (PACT). This photolability can be enhanced through both steric and electronic effects . In our group, thioether ligands have been considered with more attention for the photocaging of bioactive ruthenium polypyridyl complexes. , Their softness makes thioethers excellent ligands for ruthenium­(II) ions, and their complexes often show good thermal stability. Under blue light irradiation, several groups have shown that thioether ligands can be selectively substituted by solvent molecules, both for monodentate ligands, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, 2 is located in the hydrophobic interior of the lipid bilayer, while the positively charged centre of 3 2+ , responsible for accepting the energy, is dangling at the bilayer–water interface. 54 Therefore, it is very unlikely that 2 and 3 2+ can come in close contact to realize orbital overlap. For these reasons, we conclude that the most likely mechanism of energy transfer is Förster resonance energy transfer (FRET).…”
Section: Resultsmentioning
confidence: 99%